Dataset on LC-Q-TOF/MS tentative identification of phytochemicals in the extract of Vernonia amygdalina leaf through positive ionization - Alara, Oluwaseun Ruth; Abdurahman, Nour Hamid; Ukaegbu, Chinonso Ishmael; Hasan, Zulkafli; Kabbashi, Nassereldeen Ahmed (Elsevier Inc., 2018)
The tentative identification of bioactive compounds in the extract of Vernonia amygdalina leaf was carried out using positive ionization of Liquid chromatography-mass spectrometry quadrupole time of flight (LC-Q-TOF/MS). The positive ionization is associated with the presence of saponins, flavonoids, alkaloids, terpenoids, and glycosides. Tentative assignments of the secondary metabolites were performed by comparing the MS fragmentation patterns with Waterss UNIFY library which allows positive identification of the compounds based on the spectral match. All the metabolites compounds were estimated and presented in a BPI (Base peak intensity) plot. These data are the unpublished supplementary materials related to “Ethanolic extraction of bioactive compounds from V. amygdalina leaf using response surface methodology as an optimization tool”